Humoral and cellular immune responses after COVID-19 vaccination of lung transplant recipients and patients on the waiting list: a 6-month follow-up - Hoek, Rogier A. S.; Liu, Siqi; GeurtsvanKessel, Corine H.; Verschuuren, Erik A. M.; Vonk, Judith M.; Hellemons, Merel E.; Kool, Mirjam; Wijbenga, Nynke; Bogers, Susanne; Scherbeijn, Sandra; Rugebregt, Sharona; van Gemert, Johanna P.; et al. (Frontiers in Immunology, 2024)
Background Data on cellular response and the decay of antibodies and T cells in time are scarce in lung transplant recipients (LTRs). Additionally, the development and durability of humoral and cellular immune responses have not been investigated in patients on the waitlist for lung transplantation (WLs). Here, we report our 6-month follow-up of humoral and cellular immune responses of LTRs and WLs, compared with controls. Methods Humoral responses to two doses of the mRNA-1273 vaccination were assessed by determining spike (S)-specific IgG antibodies and neutralizing antibodies. Cellular responses were investigated by interferon gamma (IFN-γ) release assay (IGRA) and IFN-γ ELISpot assay at 28 days and 6 months after the second vaccination. Results In LTRs, the level of antibodies and T-cell responses was significantly lower at 28 days after the second vaccination. Also, WLs had lower antibody titers and lower T-cell responses compared with controls. Six months after the second vaccination, all groups showed a decrease in antibody titers and T-cell responses. In WLs, the rate of decline of neutralizing antibodies and T-cell responses was significantly higher than in controls. Conclusion Our results show that humoral and cellular responses in LTRs, if they develop, decrease at rates comparable with controls. In contrast, the inferior cellular responses and the rapid decay of both humoral and cellular responses in the WL groups imply that WLs may not be protected adequately by two vaccinations and repeat boostering may be necessary to induce protection that lasts beyond the months immediately post-transplantation.